Electrochemical Behavior of CsI in LiCl Molten Salt. (15th October 2020) - Kim, Sung-Wook; Lee, Sang-Kwon; Jeon, Min Ku; Choi, Eun-Young
Abstract : The electrochemical behavior of CsI in LiCl molten salt was investigated to identify its impact on the electrolytic oxide reduction of oxide-phase spent nuclear fuels by combined electrolysis and cyclic voltammetry experiments of LiCl-CsI in comparison with LiCl, LiCl-CsCl, and LiCl-LiI. It was found that Cs + ions were hardly involved in the cathode reaction, and reduction of Li + ions occurred dominantly in the cathode. In contrast, incorporation of I − ions induced low-potential anode reaction compared with the I − ion-free cases. Such additional electrochemical reaction resulted in the generation of I2 and/or ICl gases, which would increase a process burden for treating 129 I with exceptionally long lifetime. In this respect, separating CsI from spent nuclear fuel before the electrolytic oxide reduction is recommended for the purpose of efficient waste management.